Diseño integral de un sistema de energía solar fotovoltaica para viviendas rurales aisladas (2022)
To abord energy efficiency it is necessary to refocus the way in which end users and their network manage the use of energy. it is necessary to refocus the way in which end users and their network manage the use of energy, it is necessary to adopt means of distribution whose fundamental axes are renewable energies, taking into account that the majority of rural homes do not with access to an electrical network and those that do have an electrical network, have an intermittent service due to little maintenance and little presence of service providers, showing problems of safety, health, communication and drinking water, In this sense, for rural homes, the supply of energy to these homes that are located far from the municipal seat could be guaranteed, proposing the comprehensive design of an energy system through a photovoltaic solar panel